Acoustic–Excitonic Coupling for Dynamic Photoluminescence Manipulation of Quasi‐2D MoS2 Nanoflakes. Issue 7 (12th March 2015) - Rezk, Amgad R.; Walia, Sumeet; Ramanathan, Rajesh; Nili, Hussein; Ou, Jian Zhen; Bansal, Vipul; Friend, James R.; Bhaskaran, Madhu; Yeo, Leslie Y.; Sriram, Sharath
<x xml:space="preserve">Abstract</x> A surface acoustic wave (SAW) is shown to effectively and reversibly modulate the photoluminescence in quasi‐2D MoS2. This technique does not result in any structural or compositional change, which suggests the tremendous potential of integrating 2D materials on to SAW platforms for designing controllable, state‐of‐the‐art optoelectronic systems.